The Underground Railroad - Colson Whitehead (Doubleday Books, 2016)
Cora is a slave on a cotton plantation in Georgia. Life is hell for all the slaves, but especially bad for Cora; an outcast even among her fellow Africans, she is coming into womanhood—where even greater pain awaits. When Caesar, a recent arrival from Virginia, tells her about the Underground Railroad, they decide to take a terrifying risk and escape. Matters do not go as planned—Cora kills a young white boy who tries to capture her. Though they manage to find a station and head north, they are being hunted.